2014
DOI: 10.1101/010645
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic survey of an intragenic epistatic landscape

Abstract: Mutations are the source of evolutionary variation. The interactions of multiple mutations can have important effects on fitness and evolutionary trajectories. We have recently described the distribution of fitness effects of all single mutations for a nine-amino-acid region of yeast Hsp90 (Hsp82) implicated in substrate binding. Here, we report and discuss the distribution of intragenic epistatic effects within this region in seven Hsp90 point mutant backgrounds of neutral to slightly deleterious effect, resu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Based on previous screenings of fitness effects in different environments (26) and on different genetic backgrounds (20), and on expectations of their biophysical role, 13 amino acid-changing point mutations at 6 sites were chosen for the fitness landscape presented here (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous screenings of fitness effects in different environments (26) and on different genetic backgrounds (20), and on expectations of their biophysical role, 13 amino acid-changing point mutations at 6 sites were chosen for the fitness landscape presented here (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…This analysis showed that almost all of the variance unexplained by additivity (∼ 40%) could be attributed to epistasis, making its contribution to the phenotype comparable to that of single mutations. A large fraction of that epistasis was beneficial, in contrast with previous reports of mostly negative epistasis owing to the concavity of the scale [24,29,49], which we here circumvent by directly considering the free energy.…”
Section: Discussionmentioning
confidence: 75%
“…This analysis showed that almost all of the variance unexplained by additivity (∼ 40%) could be attributed to epistasis, making its contribution to the phenotype comparable to that of single mutations. A large fraction of that epistasis was beneficial, in contrast with previous reports of mostly negative epistasis owing to the concavity of the scale [24,29,49], which we here circumvent by directly considering the free energy.Epistasis is key to understanding the predictability and reproducibility of evolutionary paths [18,51]. Our results show how it could constrain the space of possible hypermutation trajectories during affinity maturation, with important consequences for antibody and vaccine design, as the importance of eliciting responses of antibodies that are not just strongly binding but also evolvable is being increasingly recognized [52].…”
mentioning
confidence: 75%
See 2 more Smart Citations